Augmenting antibody response to EGF-depleting immunotherapy: Findings from a phase I trial of CIMAvax-EGF in combination with nivolumab in advanced stage NSCLC - Evans, Rachel; Lee, Kelvin; Wallace, Paul K.; Reid, Mary; Muhitch, Jason; Dozier, Askia; Mesa, Circe; Luaces, Patricia L.; Santos-Morales, Orestes; Groman, Adrienne; Cedeno, Carlos; Cinquino, Aileen; et al. (Frontiers in Oncology, 2022)
Background: CIMAvax-EGF is an epidermal growth factor (EGF) depleting immunotherapy which has shown survival benefit as switch maintenance treatment after platinum-based chemotherapy in advanced non-small cell lung cancers (NSCLC). The primary objective of this trial is to establish the safety and recommended phase II dose (RP2D) of CIMAvax-EGF in combination with Nivolumab as second-line therapy for NSCLC. Methods: Patients with immune checkpoint inhibitor-naïve metastatic NSCLC were enrolled using a “3+3” dose escalation design. Toxicities were graded according to CTCAE V4.03. Thirteen patients (one unevaluable), majority with PD-L1 0%, were enrolled into two dose levels of CIMAvax-EGF. Findings: The combination was determined to be safe and tolerable. The recommended phase 2 dose of CIMAvax-EGF was 2.4 mg. Humoral response to CIMAvax-EGF was achieved earlier and in greater number of patients with the combination compared to historical control. Four out of 12 evaluable patients had objective response.